(untitled) (Research, Society and Development, 2021)
Semiochemicals, 5-methyl-nonacosane, Alkanes, Chromatography.Ants are eusocial organisms with great relative abundance and species richness. Studies on these organisms are scarce, especially in the high altitude humid forest environments of the state of Ceará. In view of this condition, an evaluation of the chemical composition of cuticular hydrocarbons (CHCs) of the species Odontomachus bauri found and recorded for the first time in this study in the tropical forest of Maranguape was carried out, based on the hypothesis that different nests have different compositions of CHCs. For this purpose, collection incursions were carried out in the region to obtain individuals from three different nests. In the laboratory, the extraction of CHCs was performed by immersing the ants in hexane for 30 minutes. After removing the ants, the extracts were subjected to drying to assess the yield of the samples. Then, the extracts were subjected to a silica gel column, before performing an analysis by gas chromatography coupled with mass spectrometry. The chromatograms obtained were analyzed and demonstrated a great similarity, showing long-chain saturated hydrocarbons, mainly represented by alkanes and methyl-alkanes. 5-Methyl-nonacosane was the component with the highest relative abundance. Statistical analysis of similarity and correlation between samples was performed using non-parametric tests. These analyzes provided sufficient statistical evidence to confirm the existence of a strong positive correlation between the samples and also a significant difference in the composition of HCCs in two of the three paired analyzes performed, thus confirming the study hypothesis.